2012
DOI: 10.1111/ijcp.12008
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of pulmonary hypertension in young adults

Abstract: In this large, observational study of young adults, pulmonary hypertension, as assessed by echocardiography, is common. Diastolic dysfunction, obesity, physical inactivity and smoking are associated with elevated pulmonary arterial pressure in young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
7
1
Order By: Relevance
“…The prevalence of PH of 6.8% in our community-based cohort is similar to the prevalence reported in large populations of mostly Caucasians evaluated by echocardiography for clinical reasons in the INCIPIT study in Italy (TR jet velocity 3m/s: prevalence of 6.6%) [27]. While one study had found AAs to have higher mean PA pressures independent of age, gender, BMI, smoking status, and presence of diastolic dysfunction [28], our findings do not support a higher prevalence of PH prevalence in AAs compared to the previous report based on the Italian cohort.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The prevalence of PH of 6.8% in our community-based cohort is similar to the prevalence reported in large populations of mostly Caucasians evaluated by echocardiography for clinical reasons in the INCIPIT study in Italy (TR jet velocity 3m/s: prevalence of 6.6%) [27]. While one study had found AAs to have higher mean PA pressures independent of age, gender, BMI, smoking status, and presence of diastolic dysfunction [28], our findings do not support a higher prevalence of PH prevalence in AAs compared to the previous report based on the Italian cohort.…”
Section: Discussionsupporting
confidence: 83%
“…Although idiopathic pulmonary arterial hypertension is more prevalent in women, to the best of our knowledge this is the first study demonstrating the increased prevalence of PH overall in women in a population-based cohort. In contrast, a relationship between gender and PA pressures was not observed in a general population of young adults [28], in normal echocardiograms performed over a decade at Massachusetts General Hospital [29], or in the Olmstead County population cohort [1]. The gender influence on PH in our cohort was independent of age, BMI, and cardiovascular and pulmonary disease, which may suggest a role of race- and gender-specific biologic factors such as estrogen and estrogen metabolites [3033] and needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…When using the same PAAT cutoff of 110 ms as in previous studies (which corresponds to a pulmonary artery systolic pressure of 46 mm Hg), the prevalence of mild to moderate pulmonary hypertension was 11% in the obese group and 36% in the MetS group ( P =0.001). PAAT was modestly correlated with RV diastolic function in the MetS and obese groups ( r =0.22, P =0.007 for TV e′; r =0.25, P =0.002 for TV e′/a′ ratio).…”
Section: Resultsmentioning
confidence: 83%
“…Higher BMI has been associated with higher pulmonary pressures (estimated by tricuspid regurgitant jet velocity) in a large echocardiography‐based cohort . Pulmonary pressures, as estimated by PAAT, also correlated with BMI in the Coronary Artery Risk Development in Young Adults (CARDIA) study, in which the prevalence of mild–moderate pulmonary hypertension, as defined by a PAAT between 70.01 and 109.9 ms, was as high as 14% . Interestingly, metabolic disease has been associated with pulmonary arterial hypertension and pulmonary venous hypertension in small studies of patients with symptomatic disease.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation